2002
DOI: 10.1159/000056285
|View full text |Cite
|
Sign up to set email alerts
|

Are Fashion Models a Group at Risk for Eating Disorders and Substance Abuse?

Abstract: Background: Few studies to date have investigated whether in fact the prevalence of eating disorders (ED) and/or use of illicit drugs is higher among models than among other groups of females. Method: A group of 63 professional fashion models of various nationalities were studied by means of self-reported questionnaires. They were compared with a control group of 126 female subjects recruited from the general population. Results: Fashion models weigh significantly less than controls, but only a small percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 10 publications
4
36
0
3
Order By: Relevance
“…It is also possible that these girls responded positively to image exposure as a result of making downward comparisons in relation to BMI. However, downward comparisons were unlikely for the majority of girls, as the average BMI ranged from 21.1 to 22.4, which is still substantially larger than the media ideal (Santonastaso et al., 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that these girls responded positively to image exposure as a result of making downward comparisons in relation to BMI. However, downward comparisons were unlikely for the majority of girls, as the average BMI ranged from 21.1 to 22.4, which is still substantially larger than the media ideal (Santonastaso et al., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…SCT may be applied to understanding changes in body image in young women following exposure to idealized female images. The socioculturally sanctioned ideal body is unrealistically tall and thin (Santonastaso, Mondini, & Favaro, 2002; Spitzer, Henderson, & Zivian, 1999), and the great majority of adolescent girls and young women do not fit this ideal, with average body sizes substantially larger than those of those females depicted in the media (Spitzer et al., 1999). Consequently, most girls are likely to engage in upward comparisons.…”
mentioning
confidence: 99%
“…While still scarce, some data do exist regarding the prevalence of unhealthy weight control behaviors (UWCB) and disordered eating among fashion models, with up to 18% of professional models reporting restriction (Preti et al, ), 31% reporting nonpurging behavior including fasting in the past month (Santonastaso, Mondini, & Favaro, ), and up to 60% reporting bulimic episodes in the previous 3 months as compared to 34% of control participants (Preti et al, ). However, findings regarding the potential higher prevalence of eating disorders among professional models have been mixed.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies have described a ‘disordered’ family system, characterized by an emphasis on dieting and physical appearance, conflict avoidance, motherly overprotection, absence of the father, and presentation of an intact family to outsiders [10, 11, 12, 13, 14, 15, 16, 17, 18]. In particular, recent case-control studies of subjects with bulimia [19]and anorexia nervosa [20]have demonstrated that these individuals exhibited greater childhood exposure to factors likely to increase the risk of dieting, and greater negative self-evaluation, even when compared to individuals with other psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%